SENSIBILIZAR PARA INCLUIR: VOVÓ FOFUXA E SUAS BONECAS DE PANO NA EDUCAÇÃO INFANTIL E ENSINO FUNDAMENTAL I (Revista Contexto & Educação, 2021)
The presence of students with physical, sensory disabilities in primary schools as well as in non-formal educational institutions is increasingly common. This article aims to present storytelling activities developed by teachers inserted in a research project that deals with teaching materials and geography teaching. The basic principle was to choose stories with a geographical character and also some classic children's literature in order to count them and then spread them through Youtube channel, facebook pages and storytelling to children using dolls of cloth. As a result, the participation of the students and teachers involved in the activity and the indicative of the potential of these ludic actions in the promotion of the awareness of the students of elementary education and the fundamental education I to the issue of respect for the other.
Keywords: Inclusive education. Didactic resources. Storytelling. Youtube channel and cloth dolls.